Successful Outcome of Pregnancy in a Diagnose Case of Autoimmune Hemolytic Anemia - Akter, Razia; Karim, Md Rezaul; Tasnim, Saria (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Autoimmune hemolytic anemia (AIHA) is a rare entity during pregnancy. The fetal risk is determined primarily by the ability of auto-antibodies to cross the placental barrier. Currently, the establishment of a standardized antenatal care in cases with AIHA remains as a pending issue. The case report we described here a case of 20-week pregnant woman with history of three spontaneous abortion and one term IUD and diagnosed as a case of Autoimmune hemolytic anemia with history of Evan’s syndrome and Idiopathic thrombocytopenic purpura . She was on regular monitoring with prednisolone therapy and showed good progress during antenatal period. Foetal parameters were also good .At 38 weeks pregnancy, a male baby was delivered by caesarian section due to PROM with BOH with PIH and there was no adverse effect during post natal period . Conclusion: Strong vigilance and monitoring during pregnancy ,childbirth puerperium is required to achieve good outcome on Autoimmune haemolytic anaemia . Bangladesh J Obstet Gynaecol, 2021; Vol. 36(2): 138-139